Glucocorticoid Receptor Maintains Vasopressin Responses in Kidney Collecting Duct Cells - Yang, Hsiu-Hui; Su, Shih-Han; Ho, Cheng-Hsuan; Yeh, Ai-Hsin; Lin, Yi-Jiun; Yu, Ming-Jiun (Frontiers in Physiology, 2022)
Water permeability of the kidney collecting ducts is regulated in part by the amount of the molecular water channel protein aquaporin-2 (AQP2), whose expression, in turn, is regulated by the pituitary peptide hormone vasopressin. We previously showed that stable glucocorticoid receptor knockdown diminished the vasopressin-induced Aqp2 gene expression in the collecting duct cell model mpkCCD. Here, we investigated the pathways regulated by the glucocorticoid receptor by comparing transcriptomes of the mpkCCD cells with or without stable glucocorticoid receptor knockdown. Glucocorticoid receptor knockdown downregulated 5,394 transcripts associated with 55 KEGG pathways including “vasopressin-regulated water reabsorption,” indicative of positive regulatory roles of these pathways in the vasopressin-induced Aqp2 gene expression. Quantitative RT-PCR confirmed the downregulation of the vasopressin V2 receptor transcript upon glucocorticoid receptor knockdown. Glucocorticoid receptor knockdown upregulated 3,785 transcripts associated with 42 KEGG pathways including the “TNF signaling pathway” and “TGFβ signaling pathway,” suggesting the negative regulatory roles of these pathways in the vasopressin-induced Aqp2 gene expression. Quantitative RT-PCR confirmed the upregulation of TNF and TGFβ receptor transcripts upon glucocorticoid receptor knockdown. TNF or TGFβ inhibitor alone, in the absence of vasopressin, did not induce Aqp2 gene transcription. However, TNF or TGFβ blunted the vasopressin-induced Aqp2 gene expression. In particular, TGFβ reduced vasopressin-induced increases in Akt phosphorylation without inducing epithelial-to-mesenchymal transition or interfering with vasopressin-induced apical AQP2 trafficking. In summary, our RNA-seq transcriptomic comparison revealed positive and negative regulatory pathways maintained by the glucocorticoid receptor for the vasopressin-induced Aqp2 gene expression.